Development and validation of LC-MS/MS method for quantification of bisphenol A and estrogens in human plasma and seminal fluid - Vitku, Jana; Chlupacova, Tereza; Sosvorova, Lucie; Hampl, Richard; Hill, Martin; Heracek, Jiri; Bicikova, Marie; Starka, Luboslav (Talanta, 2015)
Bisphenol A (BPA) is a widely known endocrine disruptor with estrogenic, antiestrogenic or antiandrogenic properties. BPA could interfere with estrogen metabolism as well with receptor-mediated estrogen actions. Both environmental BPA and estrogens may be traced in body fluids, of which, besides the blood plasma, the seminal fluid is of particular interest regarding their possible interactions in the testis. The method for simultaneously determining BPA and estrogens is then needed, taking into account that their concentrations in these body fluid may differ. Here the method was developed and validated for measurements of BPA, estrone (E1), estradiol (E2) and estriol (E3) in blood plasma and seminal plasma using liquid chromatography-tandem mass spectrometry. Due to the phenolic moiety of all compounds, dansyl chloride derivatization could be used. The analytical criteria of the method with respect to expected concentration of the analytes were satisfactory. The lower limits of quantifications (LLOQ) amounted to 43.5, 4.0, 12.7, 6.7 pg/mL for plasma BPA, E1, E2 and E3, and 28.9, 4.9, 4.5, 3.4 pg/mL for seminal BPA, E1, E2 and E3, respectively. The concentrations of individual steroids differed between body fluids. To the best of our knowledge, this is the first method that enabled the measurement of estrogens and BPA together in one run. The concentrations of E1, E2 and for the first time also of E3 in seminal plasma in normospermic men are reported.
Keywords: estron; Phenols; estrogeny; Benzhydryl Compounds; Semen; LC–MS; benzhydrylové sloučeniny; mužské pohlaví; Limit of Detection; Bisphenol A; limita detekce; endokrinní disruptory; fenoly; Estriol; Endocrine Disruptors; Humans; sperma; Tandem Mass Spectrometry; Estrogens; Estradiol; chromatografie kapalinová; tandemová hmotnostní spektrometrie; Estrone; Chromatography, Liquid; lidé; Male